2D Indium Oxide at the Epitaxial Graphene/SIC Interface: Synthesis, Structure, Properties, and Devices - Turker, Furkan; Xu, Bohan; Dong, Chengye; Labella, Michael; Nayir, Nadire; Sheremetyeva, Natalya; Trdinich, Zachary J.; Zhang, Duanchen; Adabasi, Gokay; Pourbahari, Bita; Lu, Li‐Syuan; Auker, Wesley E.; et al. (Wiley, 2025)
Abstract Scaled and high‐quality insulators are crucial for fabricating 2D/3D hybrid vertical electronic devices such as metal‐oxide‐semiconductor (MOS) based Schottky diodes and hot electron transistors, the production of which is constrained by the scarcity of bulk layered wide bandgap semiconductors. In this research, the synthesis of a new 2D insulator, monolayer InO 2 , which differs in stoichiometry from its bulk form is presented, over a large area (>300 µm 2 ) by intercalating at the epitaxial graphene (EG)/SiC interface. By adjusting the lateral size of graphene through optical lithography prior to the intercalation, the thickness of InO 2 is tuned such that it is 85% monolayer. The preference for monolayer formation of InO 2 is explained using molecular dynamics and density functional theory (DFT) calculations. Additionally, the bandgap of InO 2 is calculated to be 4.1 eV, differing from its bulk form (2.7 eV). Furthermore, MOS‐based Schottky diode measurements on InO 2 intercalated EG/n‐SiC demonstrate that the EG/n‐SiC junction transforms from ohmic to a Schottky junction upon intercalation, with a barrier height of 0.87 eV and a rectification ratio of ≈10 5 . These findings introduce a new addition to the 2D insulator family, demonstrating the utility of monolayer InO 2 as a barrier in vertical electronic devices.